Comparative study of wind farm stabilization using variable speed generator and FACTS device - Okedu, K.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (2011)
Recently, the grid codes require taking into account the reactive power of the wind farm in order to contribute to the network stability during grid fault, thus operating the wind farm as active compensator devices. This paper presents a comparative study of stabilizing a wind farm with variable speed wind turbine generator system that use doubly fed induction generator (DFIG) as the wind generator and a flexible ac transmission system (FACTS) like the static synchronous compensator (STATCOM). Simulation results show that the wind farm could be effectively stabilized with both systems, but at a reduced cost with the DFIG system.